(untitled) (Research, Society and Development, 2020)
Objectives: To describe the perception of nursing professionals about welcoming the male population in the family health strategy, to identify the actions of welcoming the male population performed by nursing professionals in the Family Health Strategy and to discuss the impact of welcoming the male population, with a focus on the health of this group by the Family Health Strategy. Methodology: a descriptive and exploratory study, with a qualitative approach, developed with 17 nursing professionals from the Family Health Strategy, in 2019, in the city of Rio de Janeiro. The data collection instrument was the semi-structured interview and, for data analysis, the content analysis technique was applied, organized according to the steps: pre-analysis, material exploration and treatment of results, inference and interpretation. Results and Discussion: They demonstrate the (non) understanding of the embracement of men by nursing professionals, showing weakness in dealing with the male population. The analysis pointed out that this difficulty is related to the absence of men in the basic unit and to the professional’s difficulty in dealing with the relational male gender perspective. This situation translates into the invisibility of this population in the basic health unit, which may also be associated with a deficit in the training of professionals in men’s health and in knowledge about the national policy for comprehensive care for men’s health. Final considerations: It is necessary to understand comprehensiveness in health from the perspective of gender, male vulnerability, among other issues, so that the reception meets the needs of the male population.